2018
DOI: 10.5430/jnep.v8n10p58
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mindfulness based stress reduction intervention on the perceived stress and burnout of RN students completing a doctor of nursing practice degree

Abstract: Background and objective: There is a vast amount of literature documenting the epidemic of stress and burnout within the nursing profession. It is well established that chronic stress contributes to burnout among nursing staff and students.  Research suggests that organizational change, curriculum adjustment, and mindfulness interventions can contribute to decreased stress and better outcomes for nurses. The objective of this study was to investigate the effect of a Mindfulness Based Stress Reduction (MBSR) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is worth noting that there is evidence for the efficacy of group therapy in reducing alexithymia and training programmes designed to increase awareness of bodily sensations and related emotions appear to be effective (Lumley et al, 2007). For example, some recent studies support the effectiveness of mindfulness programmes in reducing both alexithymia and burnout (Luken & Sammons, 2016;Norman, Marzano, Coulson, & Oskis, 2019;Turkal, Richardson, Cline, & Guimond, 2018).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…It is worth noting that there is evidence for the efficacy of group therapy in reducing alexithymia and training programmes designed to increase awareness of bodily sensations and related emotions appear to be effective (Lumley et al, 2007). For example, some recent studies support the effectiveness of mindfulness programmes in reducing both alexithymia and burnout (Luken & Sammons, 2016;Norman, Marzano, Coulson, & Oskis, 2019;Turkal, Richardson, Cline, & Guimond, 2018).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Therefore, it is necessary to use interventions based on novel and tested methods to enhance the behavioral, emotional, and cognitive characteristics of students to achieve educational and training goals. Research shows that mindfulness training effectively reduces anxiety and depression (Ellahi et al, 2018;Hoffman & Gomez, 2017;Gonzalo et al, 2016;Johnson et al, 2015;Dehestani, 2015;Gholipour Kohistani, 2017), cognitive, academic performance, social-emotional behavior, and performance (Zamani et al, 2018), perceived stress, fatigue, and burnout in students (Turkal et al, 2018), shyness (Mehrinezhad, 2017), and emotional problems (Van Son et al, 2014;Korner & White, 2014). This study aims to determine whether emotion regulation training and mindfulness skills training significantly reduce traditional and cyberbullying among students and which method is more effective.…”
Section: Introductionmentioning
confidence: 99%
“…In mindfulness, a person becomes aware of his mental method at every moment, and after being aware of the two ways of the mind, one doing and the other being, he learns to move the mind from one method to another, which requires the training of the specific behavioral, cognitive, and metacognitive strategies to centralize the attention process (15). Research has shown that mindfulness-based stress reduction training is effective on anxiety and depression (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), perceived stress and fatigue and burnout of students (29), and emotional problems (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%